Desigualdad socioespacial y segregación escolar en la ciudad de Lima (Revista Peruana de Investigación Educativa, 2021)
The purpose of this research is to analyse in depth the relationship between socio-spatial inequality and school segregation, focusing on Metropolitan Lima. First, we seek to estimate school segregation at the primary school level in each district and its relationship with its economic level, as well as the differential contribution of state and private schools and, second, to describe the variation of school segregation according to the socio-spatial distribution of three prototypical districts. For this purpose, a special data mining of the 2018 National Student Assessment (ECE) data from the Ministry of Education is performed and the Hutchens Square Root index is used. We analyse data from 113,233 students in 4th grade of Primary Education, distributed in 3,859 schools located in 41 districts of Metropolitan Lima. A strong relationship was found between socio-spatial segregation and school segregation, spatially segregating the most vulnerable students, as well as the important weight of private education in this relationship. But, also, that socio-spatial inequality does not determine segregation, there are districts that have low segregation regardless of their socioeconomic characteristics. All this leads to the conclusion that there is a need to implement public education policy measures to bravely fight segregation, combining common regulatory frameworks with differentiated interventions in different territories according to their characteristics. One of these measures should affect private education in different areas.
Keywords: Socio-spatial inequality; Basic education; Socioeconomic level; School segregation; Peru